Service gifts, collective social connection and reciprocity. (12th October 2020) - Tang, Yihui (Elina); Hinsch, Christian; Lund, Donald J.; Kharouf, Husni
Abstract : Purpose: This study aims to investigate the process of service gifting (i.e. unexpected upgrades or benefits) and examine why service gifts do not always result in firm-beneficial reciprocal behaviors from consumers. Design/methodology/approach: Through a series of three studies including both scenario-based and game-theory-based experiments, this research proposes and empirically validates a conceptual model that examines the effect of service gifts on firm-beneficial reciprocal behaviors, and the role of collective social connection and norm of positive reciprocity (NPR) in this process. Findings: The findings of this research show that the consumer's feelings of collective social connection mediate the link between the provision of service gifts and firm-beneficial outcomes. Furthermore, an individual's adherence to NPR moderates this process. Specifically, individuals with a strong adherence to NPR do not display increases in collective social connection following the receipt of a service gift. Those who are low in NPR follow the expected pattern of increased collective social connection leading to reciprocation. Research limitations/implications: Future research may further generalize the model to other situations such as high vs low context cultures. Longitudinal field experiments can be used to further investigate collective versus relational social connection, which can be either a by-product or a primary benefit derived from service delivery. Practical implications: The results of this research reveal the critical role of collective social connection which has been largely ignored in service gifting research. It encourages managers to use service gifting to directly boost consumers collective social connection. Furthermore, it offers managers insight into why service gifts do not always result in firm-beneficial outcomes because of the moderating role of NPR. Originality/value: The roles of social connection and the norm of reciprocity have been under-studied in both theoretical and empirical work on service gifting. This paper demonstrates that, contrary to traditional thought, those typically expected to reciprocate the most (i.e. high in NPR) may not realize increased collective social connection leading to reciprocation following receipt of a service gift.